Teratogenic effects of environmentally relevant concentrations of phenanthrene on the early development of marine medaka (Oryzia melastigma). (September 2020) - Zheng, Yuqi; Li, Yuejiao; Yue, Zonghao; Samreen,; Li, Zuwei; Li, Xuan; Wang, Jun
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous pollutants in marine environments and have arouse great concern since they pose adverse effects to marine ecosystem. To determine the potential impacts of environmentally relevant PAHs on early life stages of marine fish, this study exposed embryos of marine medaka ( Oryzias melastigma ) to 0, 2, 10, 50, and 250 μg/L of phenanthrene (Phe), one of the most abundant PAHs. The results demonstrated that Phe exposure decreased hatching rates, delayed hatching time of embryos, and increased deformity rate of newly-hatched larvae. Exposure to 10 and 50 μg/L Phe decreased the survival rate of marine medaka larvae at 28 days post-fertilization (dpf), and no embryo successfully hatched in 250 μg/L Phe exposure group. Morphology results showed that 10, 50, and 250 μg/L Phe exposure significantly retarded the development of embryos, and 2, 10, and 50 μg/L caused yolk sac edema and pericardial edema in newly-hatched larvae, indicating that low concentrations of Phe could induce developmental cardiac toxicity. Furthermore, the changes in the expression of heart development-related genes were determined, and the results showed that Phe-induced cardiac malformation might be related with fgf8, bmp4, smyd1, ATPase and gata4 genes. Overall, environmentally relevant PAHs could disrupt heart morphogenesis and hatching process of marine medaka, which might have profound consequences for sustainability of fish population. Graphical abstract: Image 1 Highlights: Environmentally relevant Phe increased deformity rate of marine medaka larvae. Phe exposure decreased hatching rates and delayed hatching time of embryos. Heart might be an important target organ of Phe during the fish early-life stage. Low concentration of Phe (2 μg/L) could induce developmental cardiac toxicity. Environmentally relevant PAHs may threaten the sustainability of fish population.